Cathepsin L and acute ischemic stroke: A mini-review - Ma, Linda; Wu, Silin; Gusdon, Aaron M.; Chen, Hua; Hu, Heng; Paz, Atzhiry S.; Aronowski, Jaroslaw; Savarraj, Jude P.; Kitagawa, Ryan S.; Choi, Huimahn A.; Ren, Xuefang S. (Frontiers in Stroke, 2022)
Ischemic stroke is a serious cerebrovascular event that results in cell death, blood-brain barrier dysfunction, tissue degradation, and inflammation, often leading to permanent disability or death. As the incidence of ischemic stroke continues to rise globally, it is crucial to examine the mechanisms of the various proteins and molecules contributing to worsened patient outcome and recovery. Cathepsin L, a cysteine protease known for degrading tissues in lysosomes and elsewhere, may play a role in brain tissue loss and inflammation after stroke. Studies have suggested that cathepsin L appears in the ischemic core shortly after stroke is induced. Using immunohistochemical staining, mass spectrometry, and other assays, the increase of cathepsin L in the brain was correlated with extracellular matrix and perlecan degradation after ischemic stroke. Additionally, injection of a cathepsin L inhibitor significantly reduced brain infarct size and improved functional scores. More research is needed to elucidate cathepsin L’s role in post-stroke inflammation and brain damage, in order to further explore the factors contributing to worsened patient outcome after ischemic stroke and work towards finding better therapeutic interventions.